2009
DOI: 10.1007/s10935-009-0181-0
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, Familism and Mother–Daughter Relations Among Suicidal and Non-Suicidal Adolescent Latinas

Abstract: We examined the role of acculturation, familism and Latina mother-daughter relations in suicide attempts by comparing 65 adolescents with recent suicide attempts and their mothers to 75 teens without any attempts and their mothers. Attempters and non-attempters were similar in acculturation and familistic attitudes but attempters report significantly less mutuality and communication with their mothers than non-attempters. Mothers of attempters reported lower mutuality and communication with their daughters tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 50 publications
3
72
0
2
Order By: Relevance
“…Three studies support the model, where acculturation gaps predicted higher youth substance use and externalizing problems (Martinez 2006;Schofield et al 2008;Zayas et al 2009). However, in two other studies, acculturation gaps were not associated with youth externalizing problems (Lau et al 2005;Pasch et al2006).…”
Section: Empirical Evaluations Of Acculturation and Cultural Value Gapsmentioning
confidence: 79%
See 1 more Smart Citation
“…Three studies support the model, where acculturation gaps predicted higher youth substance use and externalizing problems (Martinez 2006;Schofield et al 2008;Zayas et al 2009). However, in two other studies, acculturation gaps were not associated with youth externalizing problems (Lau et al 2005;Pasch et al2006).…”
Section: Empirical Evaluations Of Acculturation and Cultural Value Gapsmentioning
confidence: 79%
“…Supporting the argument that specific values need to be measured, Céspedes and Huey (2008) found that cultural value gaps between parents and adolescents in the perceived endorsement of traditional gender roles predicted greater adolescent depressive symptoms, but in this same study, parent-child gaps on a broad measure of acculturation were not related to depression. Additionally, mother-daughter cultural value gaps in familism were associated with greater externalizing symptoms but not internalizing symptoms in a sample of suicide-attempters and non-attempters (Zayas et al 2009). Thus, more research is needed examining specific cultural value gaps to understand how these gaps relate to adolescent functioning.…”
Section: Empirical Evaluations Of Acculturation and Cultural Value Gapsmentioning
confidence: 90%
“…Some studies have documented Latino girls' perceptions of gendered parenting practices (Raffaelli & Ontai, 2001, 2004. Nonetheless, more research is warranted to examine the differential contribution of these practices to conflicts among Latino PIB and both sons and daughters, as gendered practices and ensuing conflict might be associated with poor mental health among young Latinas (Bámaca-Colbert et al, 2012;Zayas, Bright, Álvarez-Sánchez, & Cabassa, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…For instance Zayas et al [15] conducted a case study on a 35-year old Brazilian woman named Biance to look at the relationship between trauma caused by immigration, substance abuse and suicide. Despite their interesting findings of the link between the three variables mentioned above, by no means were these findings generalizable.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their interesting findings of the link between the three variables mentioned above, by no means were these findings generalizable. However, in line with the Zayas et al [15] study, a review on immigrants from the Indian subcontinent found that family conflicts are associated with suicide among Indian female immigrants [16]. A more generalizable study examined duration of residence (in the foreign country) as a predictor of suicidality among ethnic minority immigrants [17].…”
Section: Introductionmentioning
confidence: 99%